A Deep Learning Model to Automate Skeletal Muscle Area Measurement on Computed Tomography Images - Amarasinghe, Kaushalya C.; Lopes, Jamie; Beraldo, Julian; Kiss, Nicole; Bucknell, Nicholas; Everitt, Sarah; Jackson, Price; Litchfield, Cassandra; Denehy, Linda; Blyth, Benjamin J.; Siva, Shankar; MacManus, Michael; et al. (Frontiers in Oncology, 2021)
Deep learning, convolutional neural networks, skeletal muscle, image segmentation, lung cancer, sarcopenia